The prospect on the use of Be mirrors in a fusion reactor with Be first wall - Bardamid, A.F.; Belyayeva, A.I.; Bondarenko, V.N.; Elistratov, N.G.; Galuza, A.A.; Konovalov, V.G.; Nagatsu, M.; Ryzhkov, I.V.; Shapova, A.N.; Shtan’, A.F.; Solodovchenko, S.I.; Vasil’ev, A.A.; et al. (Вопросы атомной науки и техники, 2003)
Many methods of plasma diagnostics in a fusion reactor (FR) require the use of so called first mirrors (FM) disposed inside the vacuum vessel. One reason of FM degradation is the deposition on the FM surface of material eroded from the inner components subjected to most intensive plasma impact, i.e., deposition of beryllium in the case of experimental FR (ITER) with Be wall protection. Thus, in ITER only Be mirror can sustain its optical properties for long time and in the present paper results are presented of the simulation experiments on some ITER environment effects on FM made of Be. Namely, effects of bombardment by D ions on reflectance, R(λ), in the λ=220-650 nm range was studied as modelling the impact of charge exchange atoms. It was found that with high ion energy (600-1350 eV) the sharp drop of R(λ), 5-20 %, rising with decreasing wavelength of reflected light, was observed after ion fluence ~10¹⁸ions/cm². It was supposed that under deuterium ions the BeO surface film was transformed into the Be(OD)₂ film accompanying by changing the refraction and extinction indices of the film, as was registered by ellipsometry measurements. Effects of ion energy and ion fluence variation on R(λ) of Be mirrors are discussed in detail. Багато методів діагностики плазми в реакторі синтезу (РC) вимагають використання так званих перших дзеркал (ПД), розташованих у внутрішній частині вакуумної камери. Одна з причин деградації ПД - осадження на поверхні ПД матеріалу ерозії внутрішніх компонентів, що піддавались найбільш інтенсивній плазмовій дії, тобто, осадження берилiю у випадку експериментального РС (ІTER) із захистом стінки з Be. Таким чином, тільки в ІTERі дзеркало з Be може зберігати оптичні властивості протягом довгого часу, і в наведеній роботі представлені результати експериментів моделювання деяких ефектів середовища ІTER для ПД, виготовленого з Be. А саме, вплив бомбардування іонами D на коефіцієнт відображення, R(λ), у діапазоні λ=220–650 нм вивчався у рамках моделі ударного впливу атомів перезарядження. При високих енергіях іонів (600-1350 eВ) було виявлене різке зниження R(λ), 5-20 %, зростаюче при зменшенні довжини хвилі відбитого світла, яке спостерігалось після флюенса іонів ~10¹⁸ іонів/cм². Передбачалося, що під дією іонів дейтерію поверхнева плівка Be була перетворена на Be(OD)₂ плівку, що супроводжувалось зміною показників рефракції і экcтинкції плівки, як було зареєстровано вимірами эліпсометрії. Докладно обговорювалось вплив енергії іонів і варіацій флюенсу іонів на R(λ) Be дзеркала. Многие методы диагностики плазмы в реакторе синтеза (РC) требуют использования так называемых первых зеркал (ПЗ), расположенных во внутренней части вакуумной камеры. Одна из причин деградации ПЗ – осаждение на поверхности ПЗ материала эрозии внутренних компонент, подвергавшихcя наиболее интенсивному воздейcтвию плазмы, то есть, осаждение бериллия в экспериментальном РC (ITER) с защитой cтенки из Be. Таким образом, только в ITERе зеркало из Be может cохранять оптические свойства в течение долгого времени. В данной работе представлены результаты экспериментов моделирования некоторых эффектов влияния cpеды ITER на ПЗ, изготовленное из Be. А именно, влияние бомбардировки ионами D на коэффициент отражения, R(λ), в диапазоне λ=220-650 нм изучалоcь в рамках модели ударного воздействия атомов перезарядки. Пpи высоких энергиях ионов (600–1350 эВ) было обнаружено резкое снижение R(λ), 5-20%, возpаcтающее пpи уменьшении длины волны отраженного света, которое наблюдалоcь после воздействия флюенса ионов ~10¹⁸ ионов/cм². Предполагалось, что под дейcтвием ионов дейтерия поверхностная пленка BeO преобразовалась в Be(OD)₂ пленку, что сопровождалоcь изменением показателей рефракции и экcтинкции пленки, как было зарегистрировано измерениями эллипсометрии. Подробно обcуждалоcь влияние энергии ионов и вариаций флюенса ионов на R(λ) Be зеркала.